Integration of Zakat in BPJS Kesehatan Financing for People Experiencing Poverty: Opportunities and Challenges - Nur Sulistiyaningsih; Luthfiyah Trini Hastuti; Solikhah; Burhanudin Harahap; Zeni Luthfiah; Abdusyahid Naufal Fathullah; Ramadhita (NAJAHA, 2026)
This study examines the potential integration of zakat as an Islamic social finance instrument to support the financing of the Health Care and Social Security Agency (Badan Penyelenggara Jaminan Sosial Kesehatan/BPJS Kesehatan) for poor communities in Indonesia. It aims to analyse the normative legal framework governing this integration and to identify the opportunities and challenges associated with incorporating zakat into the national health insurance system. The research employs a normative legal approach, drawing on statutory and conceptual analyses. Primary legal materials consist of laws and regulations related to zakat and social security. This study draws secondary data from reports published by the National Zakat Collection Agency (Badan Amil Zakat Nasional/BAZNAS), the Health Care and Social Security Agency (BPJS Kesehatan), and the Central Statistics Agency (Badan Pusat Statistik/BPS). Data were collected through a literature review and analysed qualitatively and interpretively by examining relevant legal provisions, fatwas, and institutional practices concerning the use of zakat for health insurance financing. The findings indicate that zakat can serve as a complementary financing instrument to assist poor (fakir), needy (miskin), and indebted (gharimin) participants in paying BPJS Kesehatan contributions. Normatively, this integration is supported by the 1945 Constitution, the 2011 Zakat Law, the 2004 National Social Security System (Sistem Jaminan Sosial Nasional/SJSN) Law, and the 2011 BPJS Law, and is further reinforced by the Indonesian Ulama/Scholars Council (Majelis Ulama Indonesia/MUI) Fatwa No. 102 of 2025. From the perspective of maqasid al-shariah, the integration reflects the objectives of protecting life (hifz al-nafs) and protecting wealth (hifz al-mal), while also offering potential to reduce the financial burden on vulnerable communities.